Book Reviews: On Machiavelli as Plebeian Theorist. Issue 161 (1st December 2019) - Stears, Marc; Barthas, Jérémie; Woodhouse, Adam
Abstract : Reading Machiavelli: Scandalous Books, Suspects Engagements, and the Virtue of Populist Politics, by John McCormick. Princeton, NJ: Princeton University Press, 2018. 288 pp. Machiavelli in Tumult. The Discourses on Livy and the Origins of Political Conflictualism, by Gabriele Pedullà. Translated by Patricia Gaborik and Richard Nybakken. Revised and updated by the author. Cambridge and New York: Cambridge University Press, 2018. xix + 284 pp. Machiavelli and the Orders of Violence, by Yves Winter. Cambridge: Cambridge University Press, 2018. 230 pp.